Business plan for a social entrepreneurship initiative - Guss, Marcela (2019)
While many Syrian refugees have entered Germany within the past two to three years, the pressure on the government to properly include these people into society is omnipresent. Although current efforts conducted by the government cannot be misprized, yet many believe these efforts are insufficient and lack tailor-made solutions. Especially vulnerable groups such as older women need proper programmes to empower them as well as include them into society. In this context, the concept of a social restaurant employing older Syrian refugee women as a tool to tackle these issues is analyzed within the framework of a business plan.